Six-membered ring systems: with O and/or S atoms - Santos, Clementina M.M. (2016)
The synthesis of O- and S-6-membered heterocycles was actively pursued in 2015. Special emphasis is given to the synthesis of natural oxygen derivatives. The chemistry of -oxoesters in the synthesis of O-, S-, and S,Oheterocycles (15CR151) and of copper-catalyzed C‒H functionalization reactions to prepare O-heterocycles has been discussed (15CR1622). Reviews on natural occurrence and biological properties of xanthone dimers (15NPR6); natural occurrence, synthesis, and biological activities of dihydrocoumarins (15OPP1); synthesis and structure–activity relationship of natural and synthetic peloruside analogs (15CC4750) and of coumarin derivatives (15EJM(101)476, 15NPR1472); and synthesis and bioactivities of 1,4-benzodioxane lignans (15NPR1369) and of chroman-4-ones (15EJM(93)539) have appeared. The synthesis and reactivity of 6-(trifluoromethyl)-2H-pyran-2-ones (15JFC36) and of furochromen- 4-ones (15EJM(90)633); synthesis and physical properties of π-expanded coumarins (15JMCC1421); and isolation, biosynthesis, synthesis, and biological activities of naphthopyranones (15NPR578) were also reviewed. An overview on unconventional terpene cyclases and their impact on biomimetic biosynthesis of terpenoids bearing pyran and chroman moieties (15AGE2604) and the chemical features, synthesis, and biological properties of mangiferin and derivatives have appeared (15MRMC582). The background and implications of natural antimalarial artemisinin in traditional Chinese medicine (15NPR1617) as well as its synthesis, biosynthesis and large-scale production (15NPR359) have been highlighted.